The mechanism of peer support on the mental toughness of adolescent swimmers: the mediating role of self-efficacy - Chen, Bingzhou; Li, Haixia; Zhang, Ruiyun (Frontiers in Psychology, 2025)
ObjectiveCurrent understanding of peer support’s role in swimmers’ mental toughness development remains limited. Guided by Bandura’s social cognitive theory, explores the relationship between peer support and the mental toughness of adolescent swimmers, along with self-efficacy’s mediating effect.MethodsThis study used a quantitative cross-sectional design. A total of 161 adolescent swimmers, aged 10–18 years, participated in the research. Data on participants’ peer support, self-efficacy, and mental toughness were collected through questionnaire surveys. The data were analyzed using hierarchical linear regression, and mediation effects were tested with the bootstrapping method.ResultsStudies have shown peer support, self-efficacy, and mental toughness showed significant intercorrelations. Mediation analysis confirmed that self-efficacy fully mediated the relationship between peer support and mental toughness: while peer support initially predicted mental toughness (β = 0.224, p < 0.01), its direct effect diminished (β = 0.107, p > 0.05) when self-efficacy (β = 0.418, p < 0.001) was included. The significant indirect effect via self-efficacy thereby highlights its role as the key mechanism through which peer support enhances mental toughness.ConclusionResearch has demonstrated that the presence of peer support is significantly positively correlated with mental toughness. Self-efficacy plays a mediating role between peer support and mental toughness.